The Marriage of Biological Fathers to Their Illegitimate Daughters: A Study of the Shafi'i Madhhab and Indonesian Positive Law - Munir, Misbahul; Syafi'I, Imam; Hannan, Abd. (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Marriage is a sacred institution in Islam and the Indonesian legal system, which requires the presence of a guardian as one of its pillars. The problem arises when a daughter is born outside the bonds of a legal marriage, causing debate about the legality of the biological father to act as a marriage guardian. This study aims to examine in depth the legal status of biological fathers as marriage guardians for extra-marital daughters, focusing on a comparative analysis between the perspective of the Shafi'i Mazhab and the provisions in Indonesian positive law. This research uses a juridical-normative method with a descriptive-qualitative approach, through a literature study of classical Syafi'iyah fiqh books, Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law, and decisions of the Constitutional Court. The results showed that according to the Syafi'i Mazhab, an extramarital child does not have a nasab relationship with his biological father, so it is not valid for him to be a marriage guardian, and guardianship is left to the judge's guardian.In Indonesian positive law, although there is recognition of the civil relationship between the child and the biological father based on Constitutional Court Decision No. 46/PUU-VIII/2010, this recognition does not include guardianship rights in marriage. The gap in this research lies in the inconsistency between the recognition of civil relationship and guardianship authority in legal practice. The findings of this research provide a normative contribution in clarifying the legal position of the guardian of extramarital children and the urgency of synchronization between Islamic law and national law in answering contemporary family problems.